Analysis of biogenic amines in probiotic and commercial salamis - Roselino, Mariana Nougalli [UNESP]; Maciel, Leonardo Fonseca; Sirocchi, Veronica; Caviglia, Matteo; Sagratini, Gianni; Vittori, Sauro; Taranto, María Pía; Cavallini, Daniela Cardoso Umbelino [UNESP] (Elsevier, 2020)
Biogenic amines (BAs) are mainly formed through decarboxylation of amino acids in fermented food, such as salami, that can occasionally accumulate high concentrations of these compounds. The BAs contents in food are related to raw materials, food microbiota or starter culture used and processing and storage conditions. This study aimed to evaluate BAs profile of salamis from the Brazilian and Italian markets and salamis fermented with probiotic starter culture using HPLC-DAD. Commercial salamis from Brazil and Italy had a great BAs variability regarding the brands, with higher levels for Brazilian samples. In addition, commercial and probiotic samples exhibited a distinct BAs profile in which the first group presented PUT, TYR and SPM, while in probiotic samples there was a predominance of PUT, TYR and CAD. The use of Enterococcus faecium CRL 183 as starter culture in salami production controlled the levels of harmful BAs (PUT, CAD, TRY and HIS) during the storage period, representing an alternative for the market to obtain healthier fermented meat products.
Keywords: Biogenic amines; E. faecium CRL 183; Fermented salami; Food quality; HPLC-DAD; Liquid chromatography